HISTOMORPHOMETRIC AND ENDOTHELIN-1 IMMUNOHISTOCHEMICAL STUDY OF HUMAN PLACENTAL VILLI CORRELATED WITH UMBILICAL CORD COILING INDEX (Iraqi Journal of Medical Sciences, 2017)
Background: Umbilical cord coiling index plays a role in predicting the pregnancy outcome and risk of low birth weight. Endothelin-1 binding sites exist on placental stem villi vessels and trophoblastic layer of the villi. Endothelin-1 is involved in regulation of the feto-placental circulation and specific trophoblastic functions.Objective:To investigate the profile of anti-endothelin-1 antibody expression in the human normal placental villi in relation to the coiling indices of the umbilical cords attached to these placentas.Methods: Normal human placentas were collected with inclusion criteria (full term newborns with normal perinatal outcome whose mothers were normal), and classified according to their umbilical cord coiling index into three groups: (N, H, and H), endothelin-1 marker used to investigate the localization of the endothelin-1 in the placental villi of each group.Results: There was a difference between the mean positivity percentage of endothelin-1 immunohistochemical reactivity in normocoiled group in comparison with hypercoiled group and hypocoiled group. There is a difference between the mean number of terminal villi in the three groups and in the perimeter of blood vessels.Conclusion: The pattern of endothelin-1 reactivity is associated with vasodilatation of the villous vascular bed to maximize the exchange function of the placenta as a physiological response to overcome the sequel of obstruction of umbilical vessels in both types of abnormal coiled cords during pregnancy.Keywords: Placental villi, umbilical cord, coiling index, normal pregnancy, endothelin-1, immunhistochemistry.Citation: Hayder J. Mubarak, Sarah A. Ahmed. Histomorphometric and endothelin-1 immunohistochemical study of human placental villi correlated with umbilical cord coiling index. Iraqi JMS. 2017; Vol. 15(2): 198-205. doi: 10.22578/IJMS.15.2.13
Keywords: Placental villi; umbilical cord; coiling index; normal pregnancy; endothelin1; immunhistochemistry